INTEGRASI PENDEKATAN METODOLOGIS DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: ANALISIS DAN APLIKASI DALAM KONTEKS MODERN - Rohman, Taufikur (Intelegensia : Jurnal Pendidikan Islam, 2024)
This study examines the integration of methodological approaches in Islamic Religious Education (PAI) learning as a response to the needs of more dynamic and relevant education in the modern era. Using a literature study method, this study collects and analyzes data from various journal articles, books, and research reports to evaluate the effectiveness of dominant traditional methods, such as lectures and memorization, which often make students passive and less involved. Contemporary approaches, including the use of digital technology and project-based learning, are introduced to increase student engagement and interaction, as well as enrich the learning process. In addition, this study suggests an interdisciplinary approach that combines Islamic teachings with social sciences and humanities, providing broader applicative and contextual insights. The results show that the integration of methodological approaches not only enriches students' learning experiences but also significantly improves understanding and application of PAI materials. Flexible curriculum development and ongoing teacher training are recommended to support the effective implementation of this approach in Islamic education.